STUDI PERILAKU KESELAMATAN KERJA DALAM PENGOPERASIAN MESIN PERCETAKAN PADA PEKERJA PT MASSCOM GRAPHY - Dwi Sutriono; Hanifa Maher Denny; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2015)
Workplace accidents are caused due to unsafe working behaviors (unsafe act), such as not wearing PPE, not follow work procedures , do not follow the safety rules and work are not careful. Number of cases of occupational accidents that occurred during the last three months commencing in 2012 was higher than the previous year at the same time. The number of workplace accidents caused by unsafe behavior, the purpose of this research to study the behavior of safety in the operation of the printing machine workers at PT Masscom Graphy. This research is a descriptive qualitative research with indepth interviews. The subjects of this study were 3 people as key informants and triangulated 2 people as informants . The results showed that the K3 has a good knowledge . Attitude of key informants did not agree with the checklist form filling obligations, as well as the availability of safety PPE are still lacking. Perceptions of supervisor existence has no influence on the main informant in the practice of K3. From this study the behavior of key informants explained that in practice it does not ignore this aspect of the form K3 wear personal protective equipment, do not fill in a checklist form that corresponds to the work performed, as well as the availability of PPE that is still in the stage of procurement. The company is expected to facilitate trade with PPE.